Rendimento da abóbora sob dois métodos de irrigação, duas qualidades de água e diferentes níveis de potássio - Santos, Márcio Davy Silva (2011)
The aim of this work was to evaluate the effect of two levels of salinity using well and channel water and levels of potassium applied in furrow and drip irrigation systems on yield and quality of pumpkin fruit. The work was conducted in an area of 64 m x 55 m located in Sector D, Lot 59 of the Curu Pentecoste Irrigated Perimeter, of the Departamento Nacional de Obras contra as Secas - DNOCS. The perimeter comprehends agricultural plots of 4.0 ha irrigated or rainfed, with a predominance of the cultures of coconut and banana. The experimental design was two-factor randomized complete-block, with thirty and five plants per plot and three plants per subplot. The primary factor consisted of three irrigation management based on Class A pan evaporation (ECA). The secondary factor consisted of five levels of potassium. It was established productivity and crop quality at various levels of management factors on irrigation and levels of potassium. The parameters evaluated were weight, diameter and number of fruits. The results allowed the following conclusions: The number of fruits per plant was determining the productivity of the pumpkin, with the highest average values of productivity and efficiency of water use were obtained through the drip system with canal water. The 10% decrease in average productivity of the pumpkin with the drip of water from the well compared to the drip of water in the channel is assigned to the electrical conductivity of well water, 54% higher than the canal water irrigation. The pumpkin crop using drip water channel showed an increase in net revenues of 11% and 232%, compared to the cultivation of pumpkin drip irrigated with well water and furrow irrigated with canal water, respectively.